2016
DOI: 10.5539/ijbm.v11n8p12
|View full text |Cite
|
Sign up to set email alerts
|

Towards Acceptance M-Learning Approach in Higher Education in Saudi Arabia

Abstract: <p>Mobile learning (m-learning) is one of the most critical technological environment of distance learning in higher education institutes. The m-learning provides a widespread access to mobile devices networks and the possibility to learn regardless of time and place, unlike other learning services that depend on the location of the user. The research objectives of this study is investigate and determine the possibility of acceptance in m-Learning and examine the main factors that affect using m-Learning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
42
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(59 citation statements)
references
References 25 publications
5
42
1
Order By: Relevance
“…This raises a question as to which kind of efforts should be made in order to increase the desired level of adoption of these services (Afshan and Sharif, 2016;Alalwan et al, 2016;Alalwan et al, 2017;Dwivedi et al, 2016).Even though the related issues of mobile internet represent worthy trends in the KSA to be considered by researchers, there is a dearth of literature which has focused on mobile internet in the KSA (i.e. Abanumy and Mayhew, 2005;Alhussain et al, 2010;Al-Khalifa, 2011;Alqahtani and Atkins, 2017;Almutairi, 2011;Alnahdi et al, 2017;Alsenaidy and Ahmad, 2012;Alwahaishi and Snášel, 2013a, b;Baabdullah, 2018;Baabdullah et al, 2016;Badwelan et al, 2016;Dwivedi et al, 2017a;Gerpott et al, 2017). This is in addition to the fact that it is important that more quantitative data are available to figure out and test the main factors predicting customer intention and adoption of mobile internet in the KSA.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…This raises a question as to which kind of efforts should be made in order to increase the desired level of adoption of these services (Afshan and Sharif, 2016;Alalwan et al, 2016;Alalwan et al, 2017;Dwivedi et al, 2016).Even though the related issues of mobile internet represent worthy trends in the KSA to be considered by researchers, there is a dearth of literature which has focused on mobile internet in the KSA (i.e. Abanumy and Mayhew, 2005;Alhussain et al, 2010;Al-Khalifa, 2011;Alqahtani and Atkins, 2017;Almutairi, 2011;Alnahdi et al, 2017;Alsenaidy and Ahmad, 2012;Alwahaishi and Snášel, 2013a, b;Baabdullah, 2018;Baabdullah et al, 2016;Badwelan et al, 2016;Dwivedi et al, 2017a;Gerpott et al, 2017). This is in addition to the fact that it is important that more quantitative data are available to figure out and test the main factors predicting customer intention and adoption of mobile internet in the KSA.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Extensive literature reviews have revealed the important trends, constructs, concepts, theories, and technology adoption models for mobile learning usage at the university level. Several studies have applied the technology acceptance model (TAM) [4,9,10] and the unified theory of acceptance and use of technology (UTAUT) model [11][12][13]. Some research has modified these models with other research models such as the theory of planned behavior [14], DeLone and McLean information systems success model [15], task-technology fit [16] and expectation-confirmation theory [17].…”
Section: Conceptual Framework Of Studymentioning
confidence: 99%
“…During the last few decades, demographic changes within Arab countries and globalizing trends around the world have contributed to new ways of thinking about society. A range of societal forces, including social media (Almujaibel, 2014), a young population studying abroad (Yusuf, Al-sharqi, & Durrani, 2015), e-learning (Badwelan, Drew, & Bahaddad, 2016;Yusuf et al, 2015), and the women's rights movement (Butters, 2009), currently challenges traditional Saudi culture and will continue to do so in the future. The younger generation in Saudi Arabia will undoubtedly play a crucial role in accepting or rejecting changes to their society.…”
Section: Introductionmentioning
confidence: 99%